Cardiovascular Health Practice among Adults in a Municipality in Kathmandu District, Nepal - Subedee, Samiksha; Sharma, Muna (Nepalese Heart Journal, 2023)
Background and Aims: Worldwide, cardiovascular diseases lead to the death of around 17.9 million annually in which 85% of those deaths is due to heart attack and stroke. However, most cardiovascular diseases are preventable with modification of behavioural risk factors. Hence, this study was conducted to find out cardiovascular health practice among adults in urban city of Kathmandu. Methods: A cross-sectional study design was used where data was collected through an in-person interview technique among randomly selected 236 adults residing in Budhanilkantha Municipality of Kathmandu District. Semi-structured interview schedule based on WHO Stepwise approach and literature review was used to collect data. Data was analysed using descriptive statistics (frequency, percentage, median, Interquartile Range) and inferences were drawn with an application of the chi-square test. Results: Among 236 samples, the majority (81.8%) of the adults had good practice of cardiovascular health. However, few adults (22%) consumed WHO recommended fruits and vegetables and only a quarter of them (36.4%) monitored blood cholesterol. Among them (24.1%) were current alcohol users and (25.4%) were current smokers. More than half (52.1%) were physically active. The practice of cardiovascular health was significantly associated with marital status (p<0.001) of the adults. Conclusion: Although, most of the adults adopted the practice to maintain cardiovascular health, their adherence to monitoring blood cholesterol, adequate intake of the recommended number of fruits and vegetables, and physical activity is low. Hence, awareness programs focusing these facets would be helpful.